2022
DOI: 10.20892/j.issn.2095-3941.2022.0337
|View full text |Cite
|
Sign up to set email alerts
|

MiR-378a-3p acts as a tumor suppressor in gastric cancer via directly targeting RAB31 and inhibiting the Hedgehog pathway proteins GLI1/2

Abstract: Objective: To improve the prognosis of patients with gastric cancer (GC), more effective therapeutic targets are urgently needed. Increasing evidence indicates that miRNAs are involved in the progression of various tumors, and RAS-associated protein in the brain 31 (RAB31) is upregulated and promotes the progression of multiple malignant tumors. Here, we focused on identifying RAB31-targeted miRNAs and elucidating their potential mechanism in the progression of GC. Methods: RAB31 and miR-378a-3p expression lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 57 publications
2
4
0
Order By: Relevance
“…22 miR-378a-3p restrains gastric cancer proliferation by directly targeting RAB31 and blocking GLI1/2. 23 Consistent with this finding, we found that miR-378a-3p serves as a tumor suppressor in TNBC. miR-378a-3p upregulation prevented TNBC cell proliferation and metastasis and increased the proportion of apoptotic cells.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…22 miR-378a-3p restrains gastric cancer proliferation by directly targeting RAB31 and blocking GLI1/2. 23 Consistent with this finding, we found that miR-378a-3p serves as a tumor suppressor in TNBC. miR-378a-3p upregulation prevented TNBC cell proliferation and metastasis and increased the proportion of apoptotic cells.…”
Section: Discussionsupporting
confidence: 87%
“…By sponging miR‐378a‐3p, lncRNA SLC2A1‐AS1 promotes cancer cell metabolism and development 22 . miR‐378a‐3p restrains gastric cancer proliferation by directly targeting RAB31 and blocking GLI1/2 23 . Consistent with this finding, we found that miR‐378a‐3p serves as a tumor suppressor in TNBC.…”
Section: Discussionsupporting
confidence: 82%
“…Previous reports have shown that the activated canonical Hh signaling pathway is involved in the carcinogenesis of GC 5,36–39 . In addition to the canonical activation of GLI by Smoothened (SMO), increasing evidence suggests that GLI transcription factors are also activated by epidermal growth factor (EGF), 40 insulin‐like growth factor (IGF), 41 TGF‐β, 42,43 mTOR, 44 RAS, 45 Notch 46 and PKC 47 .…”
Section: Discussionmentioning
confidence: 99%
“…circRNAs can be generated using a cell-free system via in vitro transcription followed by ligation. Unlike linear RNAs which are susceptible to degradation by exonucleases and hydrolysis, circRNA is covalently closed and more resistant to degradation by enzymes displaying extended half-lives relative to linear RNA (Enuka et al, 2016;X Liu et al, 2022). Owing to its stability, circRNAs are more applicable than linear RNAs in therapeutic modalities.…”
Section: Downloaded Frommentioning
confidence: 99%